A national-scale characterization of organochlorine pesticides (OCPs) in intertidal sediment of China: Occurrence, fate and influential factors. (February 2020) - Lv, Min; Luan, Xiaolin; Guo, Xiaotong; Liao, Chunyang; Guo, Dufa; Miao, Jing; Wu, Xiaqing; Zhou, Ruichen; Liu, Dongyan; Wang, Dongqi; Zhao, Yanchuang; Chen, Lingxin
Abstract: Organochlorine pesticides (OCPs) have been restricted for application for about 30 years in China. Intertidal zone is a sink for anthropogenic pollutants, and to better understand the current pollution status of OCPs in China, 324 surface sediment samples collected from 14 typical intertidal zones of China were analyzed for 22 OCPs. The total concentrations of OCPs ranged from 0.051 to 4141.711 ng/g, with DDTs and HCHs being the dominant components. Seasonal variations were not significant for most intertidal zones ( p > 0.05), while significant spatial variations ( p < 0.05) were found among 14 intertidal zones, with the highest OCPs concentrations detected in Jiulong Jiang (JLJ). The OCPs concentrations in intertidal sediments would rarely to frequently cause adverse biological effects and DDTs were the major threat. Apart from the historical usage of technical DDT and lindane, current usage of technical DDT and HCH were also implied, especially for intertidal zones such as Beidaihe (BDH) and Yingluo Wan (YLW). PCA analysis indicated that compounds within the same type of OCPs were from similar source, while different types of OCPs were generally from different sources and not used together. Our results further indicated that OCPs together with organic particles entered into the intertidal zones mainly through river input. Graphical abstract: Image 1 Highlights: This is the first national-scale study about OCPs in China's intertidal sediments. All samples in JLJ showed moderate to high risks to organisms. Fresh inputs of technical DDT and HCH still existed. Different types of OCPs were generally from different sources. OCPs in intertidal sediments were mainly from riverine input rather than local areas. Abstract : Main findings: Significant spatial variations were found among intertidal zones, with JLJ exhibiting the highest concentrations and all samples in this area showing moderate to high risks, and no decrease in DDTs concentrations was observed partly due to the existence of fresh input.